Hemisection: A conservative approach - Anshul Arora; Ashtha Arya; Rajnish K Singhal; Rachit Khatana (Wolters Kluwer Medknow Publications, 2017)
Hemisection denotes the removal of compromised root and the associated crown portion with the loss of periodontal attachment and is performed to maintain the original tooth structure and attain the fixed prosthesis. The success rate of such procedure is high. The present case report demonstrates the successful management of hemisection of 46 with occlusal rehabilitation. It was a conservative approach aiming to retain as much original tooth structure as possible against the option of extraction of the natural tooth.